La résolution des conflits matrimoniaux en situation de pluralisme juridique complexe à Koudougou, Burkina Faso - Paré, Marie-Ève (Anthropologica, 2017)
The transfer of civil legal referents in Burkina Faso generates a complex legal pluralism. This article focuses on the local consequences of this legal pluralism in the context of the resolution of matrimonial conflicts, and analyses the strategies that social actors adopt in cases of separation and divorce. Drawing on various cases studies, I discuss the problems of access to the justice system and hybrid practices that arise in the particular context of Koudougou, the third largest city, demographically, in Burkina Faso.